Synthesis of multifunctional nanocomposite material: tungstate-pillared Mg-Al hydrotalcite-like compound - Hussein, Mohd Zobir; Kormaneni, S.; Malla, P. B. (Universiti Pertanian Malaysia Press, 1993)
Hydrotalcite-like compounds (HTLC) with different cationic ratios (Mg/AI) and charge-balancing inter layer anions were prepared and characterized. The surface areas of HTLCs were found to increase with increasing Mg/AI ratio. Pure HTLCs were obtained when the Mg/AI ratio was below 7. Water adsorption properties of HTLCs show that they are microporous. BET surface areas with water and nitrogen are dependent on the Mg/AI ratio of HTLC. Tungstate-pillared HTLC (synthesized from Mg/AI=7) was prepared and characterized, resulting in higher gallery height and surface area.